Analysis of Regional Economic Values Development Based on Typology, Frequency of Visit and Population using Geographic Information System To determine Strategy Development of Semarang City Tourism Area. (April 2019) - Subiyanto, S; Yuwono, B D
Abstract: The city of Semarang has six tourism icons that have the potential as tourist attractions that continues to grow every year, namely Lawang Sewu, Sam Poo Kong, Vihara Buddhagaya Watugong, Masjid Agung Menara Jawa Tengah, Museum Maerokoco, and Kota Lama. Based on this, it is necessary to determine typology and calculate the regional economic value from year to year to determine tourism development strategies. Total Economic Value (TEV) is obtained from the sum of Travel Cost Method (TCM) and Contingent Valuation Method (CVM). TCM and CVM data are obtained from the sampling survey (respondents) in 2010 and 2018. The data processing method used is multiple linear regression analysis. Based on calculations, Total Economic Value (TEV) in 2010 and 2018 which experienced an increase was Lawang Sewu of 81.53%, Sam Poo Kong of 42.98%, Kota Lama of 49.93%, Museum Maerokoco of 64.74 %, and Menara Masjid Agung Jawa Tengah of 76.87%. While Candi Bodhagaya Watugong experienced a decrease by -4.40%. The results of the regression output that most affect the function of the average tourist area are education variables and frequency of visits. The most appropriate step to develop tourism is to increase tourism promotion, while the other steps that can be used in a row based on priority are to improve tourism facilities and infrastructure, improve the quality of tourist attractions, improve education and prevent damage to tourism sites.